On Nonexistence of Nonnegative Solutions for Some Quasilinear Elliptic Inequalities in a Bounded Domain - Salieva, Olga Alexeevna (Eurasian Mathematical Journal, 2017)
Using the test function method, we study sufficient conditions of nonexistence of nonnegative solutions for a quasilinear elliptic inequality of the form \( -div(u^r|D u|^p-2 D u) ≥ a(x)u^q|D u|^s \) in a bounded domain and its generalizations.